Some Aspects of Social Forestry in West Bengal - Lahiri, A. K. (Indian Forester, 1991)
Tree growing has become accepted landuse practice in South-Western districts of West Bengal. In other parts forestry activity is limited to planting tree as a complementary crop within the overall farming system. Though planting activity has progressed but the management of plantations is yet to catch up with the progress of afforestation. There is scope for improvement of productivity of plantations. The need of technological research for increasing productivity of forests, sociological research to evolve strategles for meaningful people's participation, farmer's training for adoption of scientifiC practice and opening of result demonstration plots for learning by seeing has been advocated.